Seroprevalence of Besnoitia besnoiti, Coxiella burnetii and Chlamydia abortus in bovine dairy herds in Northern Costa Rica - Fallas Elizondo, Daisy Elena (2025)
Besnoitia besnoiti and the zoonotic agents Coxiella burnetii and Chlamydia abortus cause reproductive diseases in cattle. There are no reports on the prevalence of B. besnoiti and C. burnetii in Costa Rica. This study aimed to determine the seroprevalence and distribution of these three agents in specialized dual-purpose dairy farms in Costa Rica’s Northern Huetar area. A descriptive cross-sectional study was conducted involving 600 animals from 40 farms (15 per farm) located in the following districts: Aguas Zarcas (5), Ciudad Quesada (9), Fortuna (4), Monterrey (2), Muelle (3), Venecia (5), and Zarcero (12). The serological analysis was performed using commercial enzyme immunoassays from IDvet (Montpellier, France). The seroprevalence for B. besnoiti was high (27.3%), with seropositive individuals found in 80% of farms and in all the districts analyzed, except in La Fortuna, with the highest prevalences in Aguas Zarcas (64%), Venecia (36.6%), and Zarcero (33.3%). The seroprevalence for C. burnetii was 16.8%, with seropositive individuals found in 70% of farms distributed across all districts, especially in Zarcero (24.6%), Ciudad Quesada (19.2%), and Aguas Zarcas (17.7%). The seroprevalence for C. abortus was 1.3%, with seropositive individuals found in only 17.5% of farms in three districts: Aguas Zarcas (3.3%), Monterrey (3.3%), and Ciudad Quesada (2.9%). Veterinary producers and the relevant authorities must be alerted to take the necessary precautions and control measures, particularly against C. burnetii and C. abortus due to their zoonotic potential. Further investigation is recommended to confirm the presence of these agents through isolation or molecular diagnosis.